THE DOPPELGANGER MOTIF IN TONI MORRISON’S BELOVED: A STUDY - Rajashree Boruah (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2020)
The concept of doppelganger in literary texts is associated mostly with the ready provision for an apparition of a living person. This German word which literally means ‘double-goer’ is brought into language and simultaneously into the literary tradition as a term first used by the novelist Joann Paul Fredrich Richter in a footnote to his novel Siebenkiis (1796). German Romanticism has meditated the development of it in the romantic writers’ struggle to reach beyond the already structured platforms for an existence and its limited possibilities, by asserting a simulacrum of characters with slippage of identity and fragmentation of self and exteriorization of an alter ego. Doppelgangers are physical projections that epitomizes the otherwise hidden, secret or unconscious self of a person. They are mostly introduced in settings that are dark and spooky immediately suggesting the horrific nature associated with doubles and it usually happens to the men of solitude and isolation. The ‘double’ is not completely identical to the original one and their differences is responsible for the dynamic tension that always exits between them. Academic pane of psychoanalysis tries to decipher in literary texts certain psychological issues, complex motives of the literary personas and layers of psychic threads that constitutes the unconscious of the texts. Day dreaming, un-mindful verbal communications, relatedness to things of distant past are mere symptoms of a psychoanalytic patient very much relevant to Sethe in Toni Morrison’s novel Beloved. The tripartite structure of human psyche constructed by Freud consisting of id, ego and superego holds the root in unravelling human behavior. The psychoanalytic concepts like alter-ego, schizophrenic fantasizing, split-personality or dissociative personality disorders help one to analyze the doppelganger motif in real life as well as literature. There is an attempt on the part of the author to explore these themes in the novel to bring to fore the janiformity of adherent contradicting perceptions and motives that surmounts a human being on usual terms.